SOPTI Meeting Abstracts 2021 - Recchioni, Alberto (Scandinavian Journal of Optometry and Visual Science, 2021)
After more than a year of blockade due to the Covid-19 pandemic, it was finally possible to return to the events in the presence. The 26th National Conference of the Italian Optometric Association (SOPTI) was held in Bologna on October 10–11, 2021. The theme of the conference was “Good practice in Optometry and Contact Lenses”, with the accent on two topics: the optometric management of the patient in old age and the progression of myopia. Four keynote speakers were invited during the conference: Prof. Rigmor C. Baraas from the University of South-Eastern Norway in Kongsberg, Prof. David B. Elliot from the University of Bradford, Dr. Fabrizio Zeri from the University of Milano Bicocca and the IACLE President, Prof. Phil Morgan, from the University of Manchester. The abstracts from accepted posters and free papers are presented here.